The evolution of lexical semantics dynamics, directionality, and drift - Carling, Gerd; Cronhamn, Sandra; Lundgren, Olof; Bogren Svensson, Victor; Frid, Johan (Frontiers in Communication, 2023)
The directionality of semantic change is problematic in traditional comparative models of language reconstruction. Compared to, e.g., phonological and morphological change, the directions of meaning change over time are potentially endless and difficult to reconstruct. The current paper attempts to reconstruct the mechanisms of lexical meaning change by a quantitative model. We use a data set of 104 core concepts in 160 Eurasian languages from several families, which are coded for colexification as well as cognacy, including semantic change of lexemes in etymologies. In addition, the various meanings are coded for semantic relation to the core concept, including relations such as metaphor, metonymy, generalization, specialization, holonymy, and meronymy. Further, concepts are coded into classes and semantic properties, including factors such as animacy, count/mass, concrete/abstract, or cultural connotations, such as taboo/non-taboo. We use a phylogenetic comparative model to reconstruct the probability of presence at hidden nodes of different colexifying meanings inside etymological trees. We find that these reconstructions come close to meaning reconstructions based on the comparative method. By means of the phylogenetic reconstructions, we measure the evolutionary dynamics of meaning loss of co-lexifying meanings as well as concepts. These change rates are highly varying, from almost complete stability to complete unstability. Change rates vary between different semantic classes, where for instance wild animals have low change rates and domestic animals and implements have high change rates. We find a negative correlation between taboo animals and change rate, i.e., taboo animals have lower change rates than non-taboo words. Further, we find a negative correlation between animacy and change rate, indicating that animate nouns have lower change rate than inanimate nouns. A further result is a negative correlation between change rate and degree of borrowing (borrowability) of concepts, indicating that lexemes that are more likely to be borrowed are less likely to change semantically. Among semantic relations, we find that metonomy is more frequent than any other change, including metaphor, and that a change from general to more specific is in all cases more frequent than the other way round.